Z prawnej problematyki umowy kontraktacji w praktyce - Suchoń, Aneta (Wydawnictwo Naukowe UAM, 2017)
The purpose of the deliberations presented in the paper was to assess the provisions governing agricultural supply contracts by looking at its practical aspects and finding an answer to the question whether an agricultural producer is adequately protected under the existing law. The deliberations were focused on the identification of the parties to the contract and its subject, the form in which the contract has been entered into, contract samples, and weather conditions that may have an impact on its performance, especially in light of the provisions or articles 622 and 623 of the Polish Civil Code when the contract obligation cannot be satisfied in full. It has been found out that in the light of the existing provisions of the Civil Code, the situation of the contracting principal is considerably stronger than that of the agricultural producer. Agricultural producers are not adequately protected although there are attempts to amend certain legal regulations existing outside the Civil Code provisions. It is then posited that new instruments should be added to the Code in order to guarantee a better balance of the interests of both parties to an agricultural supply contract.

L’obiettivo delle considerazioni è duplice. Si tratta sia di valutare la disciplina del contratto di coltivazione mostrando aspetti pratici della sua applicazione sia di rispondere alla domanda se il legislatore riesca a garantire una tutela adeguata al produttore agricolo. L’articolo si propone di determinare le parti e l’oggetto del contratto in oggetto, la sua forma e i tipi, gli effetti che le condizioni meteorologiche possono avere sulla sua realizzazione, nonché di riflettere in maniera particolare sull’applicazione degli artt. 622 e 623 del c.c. in caso di impossibilità parziale di adempiere la prestazione risultante dal contratto. Concludendo, l’autrice afferma tra l’altro che, alla luce delle disposizioni del codice civile, la situazione del soggetto contraente è decisamente più forte rispetto a quella del produttore agricolo. Il legislatore, benché cerchi di rafforzare la posizione degli agricoltori, soprattutto attraverso cambiamenti disciplinari non codicistici, non riesce a garantirgli una tutela adeguata. Alla fine l’autrice formula un postulato di introdurre nuovi strumenti nel Codice civile, atti a garantire un migliore equilibrio tra gli interessi del soggetto contraente e il produttore agricolo.
Legal issues connected with agricultural supply contracts in practice
Della problematica giuridica del contratto di coltivazione nella prassi